A new species of Amystax Roelofs, 1873 endemic to the mountainous area of the Yakushima World Natural Heritage site, Kyushu, Japan - Kojima, Hiroaki; Yôro, Takeshi (Zootaxa, 2020)
Amystax urara Kojima and Yôro, sp. nov. is described from the mountainous area of the Yakushima World Natural Heritage island, Kyushu, southwestern Japan. Adult weevils were captured on leaves of Pieris japonica var. yakushimensis and Buxus microphylla var. japonica (Ericaceae and Buxaceae, respectively). This is the second species of this genus known from the island.